2019
DOI: 10.1136/bjsports-2019-101458
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapist-led treatment for young to middle-aged active adults with hip-related pain: consensus recommendations from the International Hip-related Pain Research Network, Zurich 2018

Abstract: The 1st International Hip-related Pain Research Network meeting discussed four prioritised themes concerning hip-related pain in young to middle-aged adults: (1) diagnosis and classification of hip-related pain; (2) patient-reported outcome measures for hip-related pain; (3) measurement of physical capacity for hip-related pain; (4) physiotherapist-led treatment for hip-related pain. Thirty-eight expert researchers and clinicians working in the field of hip-related pain attended the meeting. This manuscript re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 39 publications
2
56
0
Order By: Relevance
“…Treatment options for FAI syndrome can be surgical or non-surgical. 11 Non-surgical approaches are recommended as the first line options for other musculoskeletal pain conditions (evident from clinical guidelines for osteoarthritis, 12 low back pain 13 and chronic whiplash associated disorders, 14 ) due to the higher costs and risks associated with surgery. Recently published randomised controlled trials (RCTs) comparing hip arthroscopic surgery to physiotherapist-led interventions for FAI syndrome found small 15 16 to moderate 17 between-group differences favouring hip arthroscopy, with a greater cost and risk of adverse events associated with surgery.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment options for FAI syndrome can be surgical or non-surgical. 11 Non-surgical approaches are recommended as the first line options for other musculoskeletal pain conditions (evident from clinical guidelines for osteoarthritis, 12 low back pain 13 and chronic whiplash associated disorders, 14 ) due to the higher costs and risks associated with surgery. Recently published randomised controlled trials (RCTs) comparing hip arthroscopic surgery to physiotherapist-led interventions for FAI syndrome found small 15 16 to moderate 17 between-group differences favouring hip arthroscopy, with a greater cost and risk of adverse events associated with surgery.…”
Section: Open Accessmentioning
confidence: 99%
“…A recent consensus meeting recommended individualised, exercise-based interventions as the first-line treatment for young adults with hip-related pain, however, no recommendation was made regarding one type of exercise over another. 11 Such a recommendation could not be provided because of the absence of a full-scale RCT comparing the head-to-head effectiveness of different exercise-based, physiotherapist-led interventions for FAI syndrome. [18][19][20] Thus, a physiotherapist-led intervention that compares exercise interventions needs to be developed and tested.…”
Section: Open Accessmentioning
confidence: 99%
“…You can find the three other papers from that meeting here. [1][2][3] Thirty representatives of the international clinical tendon science community met for the fifth time in Groningen (Netherlands). 4 The authors guide us on terminology, 5 how to report tendon studies (see page 627) as well as steps to developing a new patient-reported outcome measure in the field.…”
Section: Karim M Khanmentioning
confidence: 99%
“…figure1 Cam lesion as described in the femoroacetabular impingement-one element of the femoroacetabular (FAI) syndrome.…”
mentioning
confidence: 99%
“…Downloaded from Infographic measures, 6 (2) standardised measurement of physical capacity 7 and (3) physiotherapist-led treatment. 8 For this paper, the working group used a scoping review framework to search the literature for systematic reviews, intervention and observational studies (prospective or retrospective) with a study population of at least 10 young and middle-aged active adults and published in English language, peer-reviewed journals. Evidence summaries and consensus recommendations were then presented to and discussed by the whole group of IHiPRN participants.…”
mentioning
confidence: 99%